On the Union of Graded Prime Submodules: Farkhonde Farzalipour, Peyman Ghiasvand - Team, Support (Thai Journal of Mathematics, 2011)
Let G be a group with identity e. Let R be a G-graded commutative ring, and let M be a graded R-module. In this paper, we investigate finite and infinite union of graded submodules of a graded R-module M. Also, we give a number of results concerning the union of graded prime submodules.